The association between normal-range admission potassium levels in Israeli patients with acute coronary syndrome and early and late outcomes. Issue 23 (June 2016) - Shlomai, Gadi; Berkovitch, Anat; Pinchevski-Kadir, Shiran; Bornstein, Gil; ,; Leibowitz, Avshalom; Goldenberg, Ilan; Grossman, Ehud
Abstract : Abstract: Abnormal serum potassium levels are associated with an increased risk of ventricular arrhythmias and mortality in patients with acute myocardial infarction (AMI). The aim of the present study was to evaluate whether different levels of serum potassium, within the normal range, are associated with worse outcomes. The present study comprised 1277 patients with AMI and normal-range admission potassium levels (3.5–5.2 mEq/L), who were enrolled and prospectively followed up in the Acute Coronary Syndrome Israeli Survey between 2010 and 2013. Patients were divided into 4 quartiles based on admission potassium levels; "normal-low" (K ≥ 3.5 and K ≤ 3.9), "normal-moderate" (K > 3.9 and K ≤ 4.18), "normal-high" (K > 4.18 and K ≤ 4.45), and "normal-very high" (K > 4.45 and K ≤ 5.2). We analyzed the association between admission serum potassium levels and 7 days in-hospital complication rates, and 30-day and 1-year all-cause mortality rates. Patients with "normal-very high" potassium displayed increased frequency of baseline clinical risk factors and experienced a higher rate of acute kidney injury during hospitalization compared with the "normal-low" group (7.7% vs 2.4%; P = 0.002). However, the rate of in-hospital ventricular arrhythmias was similar across the range of admission potassium levels (overall P = 0.26), Multivariate analysis showed that compared with "low-normal" potassium values, patients with "normal-very high" potassium levels experienced increased risk for 30-days (adjusted hazard ratio 2.88, 95% confidence interval 1.05–7.87, P = 0.039) and 1-year all-cause mortality (adjusted hazard ratio 1.98, 95% confidence interval 1.05–3.75, P = 0.034). In patients admitted with AMI, admission serum potassium levels of 4.45 to 5.2 mEq/L are not associated with in-hospital ventricular arrhythmias, but are associated with increased short and long-term mortality.